Chrysopidae of Canada and Alaska (Insecta, Neuroptera) : revised checklist, new and noteworthy records, and geo-referenced localities - Garland, J. A.; Kevan, D. K. Mce. (Zootaxa, 2007)
The Chrysopidae of Canada and Alaska, the subject of a study since 1980, including more than 6,000 adults representing 24 species in two subfamilies, are here revised and the localities georeferenced. The number of specimens, earliest authenticated specimen, new records, flight period, and the localities supported by museum specimens are provided for each species for each province or territory of Canada, as well as the State of Alaska, USA. Localities in literature for which no specimen exists are queried. A directory of collectors is provided. Biological attributes, such as attraction to light, and plants or habitat where specimens were collected, are based on label data. Chrysopa quadripunctata Burmeister and Chrysoperla rufilabris (Burmeister) are reported for the first time from the Province of Manitoba, Canada; and, Meleoma emuncta (Fitch), for the first time from the provinces of Alberta and Saskatchewan, Canada. Nomenclatural changes include: Mallada slossonae Garland, 1996, as a new objective synonym of Dichochrysa macleodi (Adams and Garland, 1983; Mallada) syn. nov., and Dichochrysa perfecta (Banks, 1895), an emendation.